Air pollution and gender imbalance in labor supply responses: Evidence from South Korea - Han, Ahram; Kim, Tae Jong; Ten, Gi Khan; Wang, Shun (Economic Modelling, 2023)
This study investigates whether and how air pollution affects the labor supply in South Korea. In order to plausibly estimate the causal impact, we utilize the fact that air pollution in South Korea is affected by spillovers from China, mediated by wind direction. The results show that mothers tend to reduce working hours in response to the worsening air quality, although the negative impact attenuates as their children age. Surprisingly, we found no labor supply reduction for fathers. The children's vulnerability to the air pollutants and the mothers' roles as principal caregivers were the probable drivers of the results. The implication of the findings is that abatement of air pollution can help address the gender imbalance in South Korea's labor market.